Improvement Of Student Squash Ability Through The Game Situation Method - Irvan Irvan; Muhammad Akbar Syafruddin; Agus Sutriawan (STKIP Muhammadiyah Kuningan, 2023)
This research will use experimental research methods. In investigating the relationship between cause and effect, this experimental research only uses the use of a study group, not a control group. Researchers used a research method known as the One Group Pretest-Posttest method. Then given training according to the program, and after giving training for 8 weeks with 16 meetings, then it was measured again with the Squash playing skill test. This situation game method is a form of exercise that can improve the ability of athletes in playing squash which has been proven by the research that has been done. As a result, this form of training is a real contribution to the growth of athletes, especially for students who are the seeds of squash athletes in the future.